Efektivitas Penyuluh Agama Islam Dalam Mencegah Syiqaq dalam Rumah Tangga; Studi Kasus di Kantor Urusan Agama Kecamatan Medan Amplas - Haitza Iftajanah; Abdul Rahman; Sulaiman Tambah (Jurnal Ekshis, 2026)
The increasing incidence of marital conflicts leading to syiqaq (prolonged marital disputes) and divorce highlights the need for preventive efforts through Islamic religious counseling provided by the Office of Religious Affairs (KUA). This study aims to analyze the implementation of Islamic religious counseling in preventing syiqaq and to identify the factors affecting its effectiveness at the KUA of Medan Amplas District, Medan City. This research employed a qualitative field research approach. Data were collected through in-depth interviews, observations, and document analysis involving the Head of the KUA, Islamic religious counselors, married couples, and community leaders. Data were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that Islamic religious counseling has been implemented through premarital guidance (Bimbingan Perkawinan), family counseling, religious education, and mediation for couples experiencing domestic conflicts. Islamic religious counselors serve as educators, mediators, counselors, and facilitators by applying persuasive, dialogical, and problem-solving approaches. The effectiveness of counseling is influenced by socio-cultural conditions, family economic circumstances, marital communication, the influence of social media, and support from families and religious leaders.